FRI0405 Prednisone Increases Both Arterial and Venous Thrombosis in SLE. (9th June 2015) - Hickman, K.; Magder, L.; Petri, M.
Abstract : Background: An increasing number of studies have investigated factors that are associated with thrombosis in SLE. However, few have examined risk factors specific for venous thrombosis in patients with SLE and no study to date has compared the relative influence of risk factors on venous versus arterial thrombosis prospectively. Objectives: We examined the effect of traditional and disease specific risk factors on both venous and arterial thrombosis. Methods: The analysis is based on 1951 patients who were enrolled in a prospective cohort from April 1987 through September 2014. In 12, 638 person years of follow up, 189 thrombotic events were observed. We fit separate multivariable models for venous and arterial thrombosis that included variables that were most important based on the age-adjusted and preliminary regression models. Results: Table 1 includes variables that were independently associated with thrombosis. Even after controlling for all the other variables in the model, there was a strong association between recent systolic blood pressure, diabetes and current prednisone dose on both venous and arterial thrombosis. Recent cholesterol was an independent risk factor only for venous thrombosis but not arterial thrombosis. Current Plaquenil use was protective only against venous thrombosis. A history of lupus anticoagulant was associated with an increased risk of venous thrombosis, but was not significant for arterial thrombosis (p=0.17.) A history of low C3 was associated with an increased risk of venous thrombosis whilst recent low C3 was more important than a history of low C3 when considering arterial thrombosis. Conclusions: Venous or arterial thromboses are equally associated with modifiable risk factors such as blood pressure and diabetes (however only venous thrombosis was associated with cholesterol in the multivariate model). Current use of prednisone at a dose greater than 20mg increased the risk of both arterial and venous thrombosis more than any other risk factor. Disclosure of Interest: None declared